Effect of Olive Mill Wastewater and Sewage Sludge addition on growth, flowering and corms production of Freesia hybrida - نصّور, مازن; هيفا, سوسن; قاسم, رنا (Latakia University Journal -Biological Sciences Series, 2021)
A field experiment was conducted to evaluate the influence of adding treated organic residues (treated olive mill wastewater (OMW) and treated sewage sludge (TSS)) on growth, flowering and corm production of Freesia hybrida grown in calcareous soil, in Lattakia, during the seasons 2018-2019 and 2019-2020. The experiment included 5 treatments: (T1: Control without any additions, T2: mineral fertilization of NPK( 30:20:20) g\m2+ 2 Kg\ m2 of organic manure, T3: 7 l\ m2 of OMW, T4: 2,5 Kg\ m2 of TSS and T5: 3,5 l\ m2 of OMW+ 1,25 Kg\ m2 of TSS). The treatment T4 achieved close results to treatment T2 with no significant differences between these two for most studied vegetative parameters (plant height, leaf number, leaf area and leaf content of total chlorophyll). No significant differences were recorded between T2 and T5 regarding all qualitative flowering characteristics (number of spikes per plant, number of flowers per spike, length flower stalk, diameter and height of flower). Also early flowering was recorded in T4 and T5 along with longer flowering duration as compared to T2. Results also showed that all fertilization treatments were superior to the control treatment T1 for all studied parameters of vegetative growth and flowering. Treatment T5 achieved the highest percentage of cormels < 1 cm in diameter (50%) and was significantly superior to all other studied treatments.